Taxonomic placement of Onuris hauthalii (Brassicaceae: Eudemeae), based on morphology and multilocus species tree analyses, and the recognition of the new genus Alshehbazia. Issue 4 (December 2015) - Salariato, Diego; Zuloaga, Fernando
Summary Onuris hauthalii is a species distributed in Southern Argentina and Chile. Its generic assignment has been controversial, being included inEudema, Brayopsis andOnuris . In order to clarify its generic affinities, we studied its morphology and phylogenetic relationships using multilocus/multispecies coalescent species-tree analyses based on four DNA regions (ITS, trnL -F, trnH -psbA, andrps16 intron). Results show that whileO. hauthalii is related toOnuris s.s., it represents a well-differentiated lineage characterised primarily by having branched rhizomes, rosette flowering with ebracteate flowers, and latiseptate silicles. Based on the morphological and molecular evidence, we place this species in the new monospecific genusAlshehbazia . A description, morphological key, updated geographical distributions, map, and illustration are provided.